Therapy or human right? The meaning of recreation for children and youth with disabilities in the "Krembo Wings" youth movement. Issue 3 (July 2016) - Soffer, Michal; Almog-Bar, Michal
Abstract: Background: Research shows that leisure or recreation promotes health, quality of life and wellbeing. Participation in leisure is also a fundamental right of people with disabilities. Studies report disparities in leisure participation between children and youth with and without disabilities. Youth movements are a form of leisure activity, and are of particular importance in Israeli society. Objective: In this study we set out to explore how the youth movement Krembo Wings (KW) outlines the meanings of recreation for children and youth with disabilities. Our theoretical framework centers on the critical perspective of a disability study committed to disability rights. Methods: We conducted a qualitative study of KW. Data were drawn from multiple sources: published and unpublished documents, website materials, and semi-structured interviews with various key people in the movement. Data were analyzed through directed content analysis and were categorized into either the biomedical model or the social model of disability. Results: Most of our findings show that KW adopts a biomedical understanding of disability. Nonetheless, indicators of the social model, though few, were also evident. Conclusions: Although the biomedical model was found to be dominant in Israel, there are promising indicators of change. Our somewhat mixed findings might suggest that KW is at a transitional phase between biomedical thinking and a more rights-based approach.